PENGARUH PELAYANAN TERHADAP KEPUASAN ANGGOATA KOPERASI SIMPAN PINJAM ETAM MANDIRI DI SAMARINDA - -, Sutanto Daniel (EKONOMIA, 2014)
The purpose of this jurnal  is the effect of satisfaction of service to credit union members Koperasi Simpan Pinjam Etam Mandiri Samarinda.The results obtianed from the test last results obtained F 3.754 F Count>F Table 2.606.t test results obtained that the value of each variable,physical environment with 4,176 t count> t table  2,021,responsiveness to 0.902 t count< t table 2,021,reliability with -0,487 t count< t table 2,021,empathy with  -0.140 t count< t table 2,021,confidence with  0.101 t count< t table2,021 that not all variables of service quality significantly influence satisfaction of members of cooperatives.Among the five variables of service quality in the know that most influential variable is the variable physical environment,show that in the analysis of the results of the partial correlation coefficient 0.527 or 52,7%.